Proyecto de factibilidad para la creación de una empresa de seguros de vida en el cantón Atahualpa, provincia de El Oro - Zhigui Salinas, Andrea del Carmen (2024)
This curricular integration work evaluates the feasibility of establishing a life insurance company in the canton of Atahualpa, province of El Oro, Ecuador, in response to an unsatisfied demand for insurance services in the region, with the objective of providing financial protection to a population that is increasingly aware of the need to ensure family welfare. The study, which analyzes economic, technical and market feasibility, projects to sell 3,907 life insurances in five years, using a methodology that combines descriptive, exploratory and applied approaches, through surveys, direct observation and market analysis to obtain accurate and relevant data. The results reveal a significant segment of the population with the economic capacity and willingness to purchase insurance, while the absence of direct competition in the region represents a significant opportunity for business development. The financial analysis shows highly favorable indicators with a Net Present Value of $142,759.51, an Internal Rate of Return of 24.15%, a Benefit/Cost Ratio of 1,21 and an investment recovery period of 1 year and 8 months, concluding that the project is not only viable from all perspectives analyzed, but also represents a strategic opportunity to satisfy a critical need in the local community, ensuring both business success and benefit for the population of the Atahualpa canton.